L`activité de préparation pré-compétitive des entraîneurs experts en gymnastique artistique et la gestion des risques corporels : Co-construire un écosystème de pratique efficient - Rolland, C.; Roche, L. (Movement & Sport Sciences - Science & Motricité, 2025)
Acrobatic training of gymnasts prioritizes preserving bodily integrity within coaching practices. This study examines the real-time activities of expert coaches during sequences with gymnasts, aimed at refining their gymnastic skills for national and international competitions. Adopting a situated cognitive anthropology approach, the study unveils the experiential knowledge manifested in coaches` intervention activities. This is achieved by jointly documenting the coaches` behaviours and their meanings in relation to the dynamics of their concerns and perceptions of the gymnasts` successive attempts. The findings highlight scaffolding processes in gymnasts` learning activity, particularly through body manipulation activities. Subsequent unscaffolding processes are characterised by reduced coach support and the gymnast`s development of alternative resources. Technical preparation for competition, integral to body risk prevention strategies, relies on the co-construction of an efficient and shared ecosystem, serving as a resource for the joint practices of coaches and their gymnasts.